BLENDED LEARNING ORIENTED KKNI TOWARDS STUDENTS CRITICAL THINKING - Naeklan Simbolon; Eva Betty Simanjuntak; Laurensia M Perangin angin (FIP Unimed, 2019)
ABSTRACTThis study aims to determine: The Effect of KKNI-Oriented Blended Learning Models on Students' Critical Thinking Ability. The research method used in this study is a quasi-experimental pattern with nonequivalent control group design. In this study used test and non-test data collection tools. Tests were used to collect data about students' critical thinking skills in the educational philosophy course. The tests used were written tests. Pre-test and post-test are given to the experimental and control classes to measure the students' critical thinking skills. The results showed that there was a significant influence using blended learning to the students' critical thinking skills. Thus it is recommended that lecturers use the blended learning model. Keywords: Model, Blended Learning, critical thinking